Kolaborasi dan Produktifitas Penulis Jurnal Warta Perpustakaan Universitas Diponegoro Tahun 2021-2022 - Pertiwi, Sri Endah (Perpustakaan Nasional, 2024)
Collaboration and productivity of authors Journal of Undip library news aims to examine how much collaboration of authors in 2021 and 2022 and the productivity of authors whose work is published in the Journal of Library News in 2021 and 2022. Citation analysis research use the bibliometric method by measuring the bibliography using mathematical and statistical approaches. The data source is scientific research papers published in the May and October editions of The Journal Warta Perpustakaan in 2021 and the May and October editions in 2022. Data processing using Exel using the Subramanyam formula. Author productivity is calculated from how often research work is published in the Warta Perpustakaan Journal. Data verification uses statistics to test hypotheses. The results showed the level of author collaboration in the 2021 and 2022 editions of Warta Perpustakaan where collaborative authors had a lower percentage than single authors. The productivity of the authors of the Warta Perpustakaan Journal in a period of two years there were two productive authors, both UPT Library and Undip Press librarians with each writing four scientific papers.